Pendampingan UMKM Tas Sling Bag dalam Implementasi Activity-Based Costing (ABC) untuk Efisiensi Biaya Produksi - Muhammad Fadlan; Agus Ristono (Jurnal Pengabdian Pada Masyarakat METHABDI, 2026)
Inefficient production cost management is a common problem for MSMEs, particularly in the creative industry sector. The Sling Bag MSME in Bekasi experienced losses due to the lack of a structured cost recording system and suboptimal control of raw materials and labor. This activity aims to implement the Activity-Based Costing (ABC) method as a solution to improve production cost efficiency and help determine a more accurate cost of goods manufactured. The implementation method was carried out through observation, cost analysis, and simulation of the application of a simple ABC system. The results showed that the application of ABC was able to identify sources of cost waste, especially in excess raw materials and low labor productivity. Implementation of this system has the potential to increase cost efficiency by up to 10–15% and assist MSMEs in managerial decision-making.